2015
DOI: 10.1080/19420862.2015.1082016
|View full text |Cite
|
Sign up to set email alerts
|

Development of human-like scFv-Fc antibodies neutralizing Botulinum toxin serotype B

Abstract: Botulinum neurotoxins (BoNTs) are responsible for human botulism, a life-threatening disease characterized by flaccid muscle paralysis that occurs naturally by food poisoning or colonization of the gastrointestinal tract by BoNT-producing clostridia. BoNTs have been classified as category A agents by the Centers for Disease Control and Prevention. To date, 7 subtypes of BoNT/B were identified showing that subtypes B1 (16 strains) and B2 (32 strains) constitute the vast majority of BoNT/B strains. Neutralizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 68 publications
2
29
0
Order By: Relevance
“…Additional antibodies that map different epitopes especially against the light chain should be further screened to exploit more potent neutralizations. We have noted that more recent studies on human-like recombinant antibodies confirmed the neutralizing role antibodies against the light chain of related toxin (Botulimum toxin) [ 45 ] and confirmed strong synergistic effect on combining the antibodies targeting different domains [ 46 ]. The antitoxins are no longer effective once the toxin is taken up into the neurons which happen faster than the identification of a botulism case since patients develop symptoms more than three days after intoxication [ 47 ].…”
Section: Discussionmentioning
confidence: 95%
“…Additional antibodies that map different epitopes especially against the light chain should be further screened to exploit more potent neutralizations. We have noted that more recent studies on human-like recombinant antibodies confirmed the neutralizing role antibodies against the light chain of related toxin (Botulimum toxin) [ 45 ] and confirmed strong synergistic effect on combining the antibodies targeting different domains [ 46 ]. The antitoxins are no longer effective once the toxin is taken up into the neurons which happen faster than the identification of a botulism case since patients develop symptoms more than three days after intoxication [ 47 ].…”
Section: Discussionmentioning
confidence: 95%
“…For anti-BoNT/E-HC antibodies, a titer of 1/600,000 against BoNT/E3 holotoxin was observed. Finally, for anti-BoNT/E-LC antibodies, a titer of 1/600,000 against BoNT/E3 holotoxin was observed [ 51 , 73 , 74 , 75 ].…”
Section: Animal Immunization and Antibody Phage-display Library Comentioning
confidence: 99%
“…The immune-library directed against BoNT/B2-HC consisted of 1 × 10 8 independent clones and was finally packaged in M13K07 helper-phage. The immune-library directed against BoNT/B2-LC consisted of 1.1 × 10 8 unique clones and was finally packaged in M13K07 phage [ 74 ]. The immune-library directed against BoNT/E3-LC consisted of 9.6 × 10 8 independent clones with a full-size insert rate of 88%.…”
Section: Animal Immunization and Antibody Phage-display Library Comentioning
confidence: 99%
See 1 more Smart Citation
“…An antibody directed against BoNT/E LC, which was selected using the biochemical assay (based on in vitro inhibition of the endopeptidase activity), proved to have a highly neutralizing potency in vivo [ 13 ]. Similarly, antibodies against BoNT/A and BoNT/B LCs, which were also selected by in vitro assays [ 22 ], were neutralizing in vivo when presented in combination with antibodies against the HC of the corresponding toxin serotype [ 12 ].…”
Section: Introductionmentioning
confidence: 99%